2022
DOI: 10.3390/ijerph192315850
|View full text |Cite
|
Sign up to set email alerts
|

A Global Survey of Ethnic Indian Women Living with Polycystic Ovary Syndrome: Co-Morbidities, Concerns, Diagnosis Experiences, Quality of Life, and Use of Treatment Methods

Abstract: Background: Polycystic ovary syndrome (PCOS) is a common endocrinopathy that is highly prevalent in women of Indian ethnicity. Clinical practice guidelines do not adequately consider ethnic–cultural differences in the diagnosing and care of women with PCOS. This study aimed to understand co-morbidities, key concerns, quality of life (QoL), and diagnosis experiences of ethnic Indian women living with PCOS. Methods: Global online survey of ethnic Indian women of reproductive age living with PCOS. Results: Respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In the past few years, studies have been reporting the lived and living experiences of those with PCOS. Many studies have highlighted this syndrome's distressing effects on multiple aspects of life [7][8][9][10]. A review showed that Health-Related Quality of Life (HRQoL) scores were consistently reduced in those living with PCOS [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, studies have been reporting the lived and living experiences of those with PCOS. Many studies have highlighted this syndrome's distressing effects on multiple aspects of life [7][8][9][10]. A review showed that Health-Related Quality of Life (HRQoL) scores were consistently reduced in those living with PCOS [11].…”
Section: Introductionmentioning
confidence: 99%